Relation Between Health Beliefs and Medications Adherence in Patients with Hyperlipidemia - Leila Mardanian-Dehkordi (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Hyperlipidemia is one of the most important factors in progression of coronary heart diseases, because of the importance of lipid control for preventing heart disease; this study has done to explore the relation between health beliefs and medications adherences in patients with hyperlipidemia. Methods: This Correlation study has done in 82 patients with hyperlipidemia. For obtain information used a questionnaire with three parts; demographic characters, adherence to medications and health beliefs. The data analyzed by Descriptive and analytical statistical tests. Results: Findings same as some studies showed relationship between health beliefs and adherences to medications in patients with hyperlipidemia (P<0.05) with high health beliefs, adherence to medication increased. Conclusion: For increasing adherence to medication, some strategies must provide for self efficacy and educational programs must be done with relationship between patient and health provider. Notice to the importance of high cholesterol and its relation with heart disease will increase adherence to medication.